Lipid-lowering response in subjects with the p.(Leu167del) mutation in the APOE gene. (March 2019) - Bea, Ana M.; Lamiquiz-Moneo, Itziar; Marco-Benedí, Victoria; Mateo-Gallego, Rocio; Pérez-Calahorra, Sofía; Jarauta, Estíbaliz; Martín, César; Cenarro, Ana; Civeira, Fernando
Abstract: Background and aims: The aim of this work was to compared the effect of lipid lowering drugs among familial hypercholesterolemia (FH) subjects with a functional mutation in LDLR ( LDLR FH) and FH with the p.(Leu167del) mutation in APOE . Methods: We retrospectively selected all adults with the p.(Leu167del) mutation on lipid-lowering treatment (n = 22) attending the Lipid Unit at the Hospital Miguel Servet. Age and sex matched LDLR FH from the same Unit were randomly selected as a control group (n = 44). Results: The mean percentage reduction in LDLc was significantly higher in the p.(Leu167del) carriers (−52.1%) than in the LDLR FH (−39.7%) ( p =  0.040) when on high intensity statins. Similar differences between groups were observed in non-HDLc −49.4% and −36.4%, respectively ( p  = 0.030). Conclusions: Subjects with p.(Leu167del) mutation have a higher lipid-lowering response to statins with or without ezetimibe than LDLR FH. This supports the use of genetics for a more efficient management of FH. Highlights: The p.(Leu167del) mutation in APOE has been described as a new cause of familial hypercholesterolemia (FH). The p.(Leu167del) carriers were on significantly lower dose of statin than LDLR FH. The p.(Leu167del) carriers had higher lipid-lowering effect to statins than LDLR FH. Our results support the use of genetics for a more efficient management of FH.